Differences and disparities over time: Black and White families investigated by Ontario's child welfare system. (September 2020) - Antwi-Boasiako, Kofi; King, Bryn; Fallon, Barbara; Trocmé, Nico; Fluke, John; Chabot, Martin; Esposito, Tonino
Abstract: Background: Black-White disparities in child welfare involvement have been well-documented in the United States, but there is a significant knowledge gap in Ontario about how and when these disparities emerge. Objective: This paper compares incidence data on Black and White families investigated by Ontario's child welfare system over a 20-year period. Methods: Data from the first five cycles of the Ontario Incidence Study of Reported Child Abuse and Neglect (OIS) (1993–2013) were used to examine trends in child maltreatment investigations involving Black and White families. Incidence rates were calculated. T -tests were conducted to assess statistically significant differences between and within cycles. Population and decision-based enumeration approaches were also used to examine child welfare disparities. Results: The incidence of investigations involving White families almost doubled between 1998 and 2003, but for Black families the incidence increased almost fourfold during the same period. These increases and the difference between Black and White families in 2003 were statistically significant. The results further indicate that Black families experience disparate representation in Ontario's child welfare system over time for most service dispositions. Conclusions: Several possible explanations are offered for the study's outcome, including changes in risk related to social safety net, the threshold for risk of harm, and bias and racist institutional policies and practices. This study invites policy-makers and child welfare authorities to rethink service delivery in addressing the disparate representation of Black families in the child welfare system.